Lecture on the Cyprus Conflict, peace negotiations and future scenarios in Cyprus - Sözen, Ahmet (My University, 2013)
[Abstract Not Available]
Lecture on the Cyprus Conflict, peace negotiations and future scenarios in Cyprus. Lecture was given by Prof. Ahmet Sözen to AISEC Students - EasternMediterranean University , July 2013.
Keywords: Cyprus Conflict, Cyprus Future Scenarios; Cyprus Problem; Peace negotiations